ANALISIS BIG DATA SENTIMEN PUBLIK TERHADAP IMPLEMENTASI KEBIJAKAN MAKAN BERGIZI GRATIS DI INDONESIA - Nikki Prafitri; Feriyansah Adi Saputra; Teodora Maelani Setiyawati; Gema Rheksa Maulana Ibrahim (Program Studi Administrasi Negara Universitas Serang Raya, 2025)
Seek the public interest is a form of government responsibility in handling various public interests in various policy lines. This is done by observing public discussions related to the performance of policies carried out by the government. The Free nutritious meals (MBG) policy is a manifestation of efforts to meet the public interest with the aim of improving the quality of nutrition in children, although in its implementation it still faces many challenges such as poisoning. The purpose of this study is to find out the public sentiment on the implementation of the MBG policy in Indonesia by using the Big Data analysis research method using X. The results of the study show that the public sentiment on the implementation of the policy is neutral. Then negative sentiment is more dominant than positive which shows that public assessment of the implementation of MBG is considered ineffective, because there are still rampant cases of poisoning and inadequate planning, implementation and supervision. In addition, political communication from the government that is not in harmony between the claimed success and the fact of policy implementation on the ground makes negative sentiment from the political sector more dominant. However, positive sentiment shows that the public considers the MBG program to be beneficial if there are significant improvements ranging from MBG and SPPG kitchen planning, implementation and adequate supervision from policy implementers.